2019
DOI: 10.3390/polym11010165
|View full text |Cite
|
Sign up to set email alerts
|

Layer-by-Layer Assembly and Electrochemical Study of Alizarin Red S-Based Thin Films

Abstract: Electroactive organic dyes incorporated in layer-by-layer (LbL) assemblies are of great interest for a variety of applications. In this paper, Alizarin Red S (ARS), an electroactive anthraquinone dye, is employed to construct LbL (BPEI/ARS)n films with branched poly(ethylene imine) (BPEI) as the complementary polymer. Unconventional LbL methods, including co-adsorption of ARS and poly(4-styrene sulfonate) (PSS) with BPEI to assemble (BPEI/(ARS+PSS))n, as well as pre-complexation of ARS with BPEI and further as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 67 publications
(70 reference statements)
0
1
0
Order By: Relevance
“…Incorporated in LbL layers electroactive dyes have also received substantial attention. It was shown that the way to incorporate electroactive anthraquinone dye to LbL films strongly influences its electrochemical properties and chemical properties [25]. Metachromic cationic dye methylene blue was investigated for organization in the LbL framework [26].…”
Section: Incorporation Of Dyes In Layer-by-layer (Lbl) Coatings-bringing Multifunctionality Through Organic Moietiesmentioning
confidence: 99%
“…Incorporated in LbL layers electroactive dyes have also received substantial attention. It was shown that the way to incorporate electroactive anthraquinone dye to LbL films strongly influences its electrochemical properties and chemical properties [25]. Metachromic cationic dye methylene blue was investigated for organization in the LbL framework [26].…”
Section: Incorporation Of Dyes In Layer-by-layer (Lbl) Coatings-bringing Multifunctionality Through Organic Moietiesmentioning
confidence: 99%